Intercropping of medicinal and aromatic crops in adult coconut garden under Brahmaputra valley region of Assam - Nath, J.C.; Deka, K.K.; Saud, B.K.; Maheswarappa, H.P. (Journal of Plantation Crops, 2014)
A field experiment conducted at Horticultural Research Station, Kahikuchi of Assam Agricultural University revealed the performance of medicinal and aromatic plants grown as intercrops in 32 year old Assam Green Tall coconut garden. There were three medicinal plants viz., sarpagandha (Rauvolfia serpentina), pipali (Piper longum) and vedailota (Paederia foetida) and two aromatic plants viz., citronella (Cymbopogon winterianus) and patchouli (Pogostemon cablin) in the experiment. The yield of all the medicinal and aromatic plants grown as intercrop in coconut garden were found to be reduced compared to their sole crop yields. The reduction in yield was less in patchouli (5.2%), followed by vedailota (7.0%), sarpagandha (8.9%), pipali (9.0%) and citronella (16.8%). The nut yield of coconut improved with intercropping with medicinal and aromatic crops. The piperine content in pipali, alkaloids in sarpagandha and essential oil content in patchouli were significantly reduced when grown as intercrops in coconut garden as compared to sole crop. However, the iridoid glycosides in vedailota and essential oil content in citronella were not significantly influenced by intercropping. Intercropping system of growing with patchouli under coconut recorded the highest net income (`178,089 ha-1) and B:C ratio (3.26) followed by sarpagandha (`157,484 ha-1 and 3.09), pipali (`113,118 ha-1 and 2.62), citronella (` 107,432 ha-1 and 2.40) and vedailota (`100,382 ha-1 and 2.36). Hence, intercropping of patchouli, sarpagandha and pipali with coconut can be recommended for Assam condition.